Cellulose modified polyurethane foam with high cohesion and application

Through the preparation of cellulose-modified polyurethane foam, gel reaction and air emitting reaction, the problem of poor toughness of polyurethane foam is solved, and the cell stability and cohesion are improved, and it is suitable for high-demand electronic equipment.

CN119285889APending Publication Date: 2025-01-10HUBEI XIANGYUAN NEW MATERIAL TECH INC
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411257441.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-10

Smart Images

  • Figure BDA0005034511410000151
    Figure BDA0005034511410000151
  • Figure BDA0005034511410000161
    Figure BDA0005034511410000161
Patent Text Reader

Abstract

The invention belongs to the technical field of foaming materials, and particularly relates to cellulose modified polyurethane foam with high cohesion, a preparation method and application. The cellulose modified polyurethane foam provided by the invention is obtained by uniformly mixing cellulose or a derivative thereof, isocyanate, an amine catalyst, a foam stabilizer, polyether polyol, an organic metal catalyst and deionized water, heating and curing, wherein the cellulose or the derivative thereof is non-fat-soluble cellulose or a derivative thereof. The cellulose modified polyurethane foam has the characteristics of stable pores, uniform pore diameter, high toughness, high cohesion and compression resistance, and is suitable for portable electronic equipment and precision electronic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of foaming materials, and more specifically, relates to a cellulose-modified polyurethane foam with high cohesion and its application. Background Art

[0002] Polyurethane foam materials are widely used in electronic equipment, automobiles, machinery, new energy and other industries. With the continuous application and development of materials, the industry has put forward more and more stringent requirements on the performance of polyurethane foam materials, such as mechanical strength, functionality (such as waterproofness, insulation, compression resistance), etc., which has prompted the foam material industry to develop in the direction of intersection with other material specialties.

[0003] The most important application field of polyurethane foam materials is the field of electronic equipment, especially portable electronic equipment and precision electronic equipment. The key components of these devices are precise and fragile, and polyurethane foam materials with cushioning properties and high cohesive properties are required to play a protective or connecting role. However, the molecular structure of existing polyurethane foams has poor toughness, poor uniformity and stability of pores. When subjected to external tension or shear stress, the molecular structure of the foam is not enough to support macroscopic elastic deformation. The use of polyether polyols with more flexible segments helps to form separated segments of different lengths in the molecular structure of the foam, thereby increasing the tensile stress and shear stress of the foam. However, such polyether polyols cause the viscosity of the foam reaction system to be low, making the foam body loose and not firm, and the regulation cost is high. The use of chain extenders containing flexible segments can increase the crosslinking degree of the foam and enhance its stress resistance, but the hardness of the foam is also affected. Excessive hardness limits the application of foam in portable electronic devices and precision electronic devices.

[0004] In summary, the production of polyurethane foam needs to take into account parameters such as the viscosity of the reaction system, the stability and uniformity of the pores of the finished product, the compression strength, and the cohesion. In view of these parameter requirements, providing a simple and highly executable technical solution is the focus of research and improvement in the foaming material industry. Summary of the invention

[0005] In view of the defects of the prior art, the purpose of this application is to provide a cellulose-modified polyurethane foam with high cohesion and its application, aiming to solve the problems that the existing polyurethane foam has poor toughness, cannot balance the cushioning performance and cohesion performance, and is not suitable for portable electronic devices and precision electronic devices.

[0006] To achieve the above-mentioned purpose, the present application provides a cellulose-modified polyurethane foam with high cohesion, which is obtained by mixing cellulose or its derivatives, isocyanate, amine catalyst, foam stabilizer, polyether polyol, organic metal catalyst and deionized water and then heating and curing;

[0007] The cellulose or its derivative is non-fat-soluble cellulose or its derivative.

[0008] Preferably, the molar ratio of the hydroxyl group of the non-fat-soluble cellulose or its derivative to the isocyanate group of the isocyanate is (5-10):100.

[0009] Preferably, the viscosity of the polyether polyol is 300 mPa.s to 1200 mPa.s.

[0010] More preferably, the molar ratio of the hydroxyl value of the polyether polyol to the isocyanate group of the isocyanate is (90-95):100.

[0011] Preferably, the polyether polyol is selected from one or more of polyethylene oxide glycol with 1,4-butanediol as initiator, polyethylene oxide triol with glycerol as initiator, polypropylene oxide triol with glycerol as initiator and polyethylene oxide-propylene copolymer glycol with ethylene glycol as initiator.

[0012] Preferably, the isocyanate is one or more of toluene diisocyanate, liquefied diphenylmethane diisocyanate and hexamethylene diisocyanate.

[0013] Preferably, the added amount of the deionized water is 0.3 wt % to 0.7 wt % of the polyether polyol.

[0014] Preferably, the amount of the amine catalyst added is 1.5wt% to 3wt% of the deionized water. The amine catalyst is selected from one or more of triethylenediamine, N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl) ether, N,N,N',N'-tetramethylethylenediamine, triethylamine, N-ethylmorpholine, N-methylmorpholine, N,N-dimethylbenzylamine, N,N,N',N",N'-pentamethyldiethylenetriamine, N,N-dimethylethanolamine, N,N'-diethylpiperazine, N,N'-diethyl-2-methylpiperazine and triethanolamine.

[0015] Preferably, the addition amount of the above-mentioned organometallic catalyst is 0.005wt% to 0.007wt% of the above-mentioned polyether polyol. The above-mentioned organometallic catalyst is selected from one or more of organozinc compounds, organotin compounds and organobismuth compounds.

[0016] Preferably, the amount of the foam stabilizer is 4wt% to 7wt% of the total raw materials for preparing the cellulose-modified polyurethane foam. The foam stabilizer is selected from one or more of bihydroxypropyl silicone oil, Y-10366 and gelatin.

[0017] Preferably, the mixing steps are as follows:

[0018] The non-fat-soluble cellulose or its derivative and deionized water are mixed and allowed to stand, and then isocyanate, an amine catalyst and a foam stabilizer are added and mixed to obtain a first mixed material;

[0019] The polyether polyol and the organic metal catalyst are mixed evenly and then stirred and mixed with the first mixed material to obtain a second mixed material.

[0020] Preferably, the steps of heating and curing are as follows:

[0021] The second mixed material is heated and solidified to obtain cellulose-modified polyurethane foam.

[0022] Preferably, the temperature of the heating and curing is 80° C. to 110° C., and the time of the heating and curing is 15 min to 20 min.

[0023] The present application also provides the use of the above-mentioned cellulose-modified polyurethane foam in electronic devices.

[0024] In general, the above technical solutions conceived by this application have the following technical advantages compared with the prior art:

[0025] (1) The cellulose-modified polyurethane foam provided in the present application is obtained by mixing cellulose or its derivatives, isocyanate, amine catalyst, foam stabilizer, polyether polyol, organic metal catalyst and deionized water and then heating and curing, wherein the cellulose or its derivatives are non-fat-soluble cellulose or its derivatives. The cellulose-modified polyurethane foam has stable pores, uniform pore size, high toughness, high cohesion and compression resistance, and is suitable for portable electronic devices and precision electronic devices.

[0026] (2) The present application prepares a polyurethane foam having a non-fat-soluble cellulose or a derivative thereof and mixed with deionized water, and then mixed and stirred with isocyanate, an amine catalyst and a foam stabilizer, so that the water-containing cellulose or a derivative thereof particles are fully dispersed in the first mixed material. At the same time, the water molecules are fully captured by the water-retaining property of the cellulose or a derivative thereof, so that the first mixed material system starts a foaming reaction in advance in this environment. When the carbon dioxide gas generated by the foaming is uniform and slightly dissipated, a mixed polyether polyol and an organic metal catalyst are added to carry out a gel reaction. At the same time, the cellulose or a derivative thereof also reacts with the isocyanate, so that the cross-linking degree of the foam is improved, and the viscosity around the cellulose or a derivative thereof increases rapidly, which plays a role in stabilizing the foam. After heating and curing, a cellulose-modified polyurethane foam having stable cells, uniform pore size, high cohesion and anti-compression is obtained.

[0027] (3) The present application provides a method for preparing high-toughness polyurethane foam with a simple scheme and high feasibility by regulating the hydroxyl value of non-fat-soluble cellulose or its derivatives and the molar ratio of isocyanate groups of isocyanate, as well as the viscosity of polyether polyol, etc., to coordinately regulate the foaming process and gelling process of the foam reaction system. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0029] The purpose of this application is to prepare a polyurethane foam with stable and uniform pores, high toughness, high cohesion, and compression resistance that can be used in portable electronic devices and precision electronic devices. Initially, a polyether polyol with more flexible segments or relatively low hydroxyl values ​​was selected to cause the molecular structure of the foam itself to form separated segments of different lengths, forming separated microcrystalline phase regions, increasing the tensile stress and shear stress of the foam, and improving the toughness of the foam. However, experiments have found that the use of the above-mentioned polyether polyols will reduce the initial viscosity of the reaction system, resulting in the foam body being loose and not firm. When subjected to external tension or shear stress, the molecular structure of the foam is not sufficient to support macroscopic elastic deformation, and the toughness of the foam molecular segments is low, which seriously affects the cohesive performance of the foam, and the regulation cost is high. In addition, too low viscosity is not conducive to the formation of uniform pores, and affects the uniform and stable dispersion of the pores, making it impossible for the microscopic pores to effectively disperse the tensile stress and prevent temporary defects caused by stress concentration. In addition, attempts were made to use chain extenders with flexible chain segments such as 1,4-butanediol to increase the crosslinking degree and crystallization tendency of the foam. Experiments have found that the above chain extenders significantly increase the hardness of the foam by increasing the crosslinking degree of the foam and thereby increasing the foam's ability to withstand stress. Excessive hardness makes the foam unsuitable for use in portable electronic devices and precision electronic devices. How to take into account the initial viscosity of the reaction system, the stability and uniformity of the foam pores, high cohesion and compressive strength in the production process of the foam is a key technical problem to be solved in this application. Based on this, the present application provides a cellulose-modified polyurethane foam with high cohesion, which is obtained by mixing cellulose or its derivatives, isocyanates, amine catalysts, foam stabilizers, polyether polyols, organometallic catalysts and deionized water and then heating and curing;

[0030] The cellulose or its derivative is non-fat-soluble cellulose or its derivative.

[0031] In the present application, the reaction of isocyanate and polyether polyol is the gel reaction of the foam system, and the reaction of isocyanate and deionized water is the gasification reaction of the foam system. The gel reaction and the gasification reaction are combined to form a polyurethane foam with a certain pore structure. A small amount of cellulose or its derivatives are added in the present application as non-fat-soluble solid particles, which will not dissolve after being stirred and mixed with the isocyanate system, but form highly dispersed suspended particle units. Synergistically, most water molecules in the foam system can be captured and adsorbed on the surface of solid particles, and the gasification reaction of deionized water and isocyanate is completed on the surface of solid particles. According to the principle of phase interface reaction, the reaction process depends on the solid-liquid surface reaction kinetic trend of isocyanate and water, that is, the overall rate of gasification can be accurately controlled by adjusting the content of deionized water, so as to achieve the stable and controllable gasification process of the foam, the uniform and controllable gasification and foaming of the foam, and ensure the uniform consistency of the pores inside the foam. In addition, isocyanate itself will also react with the alcohol hydroxyl group of cellulose or its derivatives. The reaction process follows the interfacial reaction kinetics of the solid-liquid surface. At the same time, the migration of water and the rapid gassing process of water molecules and isocyanate make the activation energy of the reaction decrease with the increase of deionized water content, thereby accelerating the reaction rate of cellulose or its derivatives and isocyanate, prompting the viscosity of the system to rise rapidly within a certain period of time, preventing the bubble wall from continuing to thin, playing a role in stabilizing the foam, and ensuring the stability and uniformity of the pores around the microparticle units. Ultimately, the pores of the foam as a whole are uniform, evenly dispersed and stable. At the same time, it can further improve the cross-linking degree of the foam, improve the overall cohesion of the foam, and effectively control the hardness and toughness of the foam.

[0032] In the present application, the molar ratio of the hydroxyl group of the above-mentioned non-fat-soluble cellulose or its derivatives to the isocyanate group of the above-mentioned isocyanate is (5-10):100, so that the non-fat-soluble cellulose or its derivatives can be evenly dispersed without agglomeration, thereby ensuring the smooth progress of the reaction and being able to prepare a foam with high cohesion, which meets the use requirements of portable electronic devices and precision electronic devices.

[0033] In some embodiments, the above-mentioned non-fat-soluble cellulose or its derivative is selected from one or more of cellulose, methyl cellulose, hydroxypropyl cellulose, carboxymethyl cellulose and hydroxyethyl cellulose. The present application does not specifically limit the source of the above-mentioned non-fat-soluble cellulose or its derivative, and it can be prepared by commercial products well known to those skilled in the art or by preparation methods well known in the art.

[0034] In some embodiments, the viscosity of the polyether polyol is 300-1200 mPa.s, specifically, it can be 300 mPa.s, 700 mPa.s, 800 mPa.s, 1200 mPa.s, to ensure that cellulose or its derivatives can be evenly dispersed, without forming microparticle groups, and without affecting the stability and uniformity of bubbles during the gasification process. Based on this, in some embodiments of the present application, the molar ratio of the hydroxyl value of the polyether polyol and the isocyanate group of the isocyanate is (90-95): 100. In a specific embodiment of the present application, the molecular weight of the polyether polyol is 600-1000, selected from one or more of polyethylene glycol with 1,4-butanediol as the initiator, polyethylene triol with glycerol as the initiator, polyethylene triol with glycerol as the initiator, and polyethylene-propylene copolymer glycol with ethylene glycol as the initiator.

[0035] In some embodiments, the isocyanate is one or more of toluene diisocyanate, liquefied diphenylmethane diisocyanate and hexamethylene diisocyanate.

[0036] In some embodiments, the amount of the deionized water added is 0.3 wt% to 0.7 wt% of the polyether polyol. In a specific embodiment of the present application, the amount of the deionized water added is 0.3 wt% to 0.5 wt% of the polyether polyol.

[0037] In the present application, the above-mentioned amine catalyst is used to catalyze the gas generation reaction in the foam synthesis process, such as but not limited to one or more of triethylenediamine, N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl) ether, triethylamine, N,N,N',N'-tetramethylethylenediamine, N-ethylmorpholine, N-methylmorpholine, N,N-dimethylbenzylamine, N,N,N',N",N"-pentamethyldiethylenetriamine, N,N'-diethylpiperazine, N,N'-diethyl-2-methylpiperazine, N,N-dimethylethanolamine and triethanolamine. In some embodiments, the addition amount of the above-mentioned amine catalyst is 1.5wt% to 3wt% of the above-mentioned deionized water. In a specific embodiment of the present application, the addition amount of the above-mentioned amine catalyst is 2wt% to 3wt% of the above-mentioned deionized water.

[0038] In some embodiments, the amount of the foam stabilizer added is 4wt% to 7wt% of the cellulose modified polyurethane foam system. In a specific embodiment of the present application, the amount of the foam stabilizer added is 4wt% to 5wt% of the cellulose modified polyurethane foam system. In some embodiments, the foam stabilizer is one or more of bihydroxypropyl silicone oil, Y-10366 and gelatin.

[0039] In some embodiments, the amount of the organic metal catalyst added is 0.005wt% to 0.007wt% of the polyether polyol. In some embodiments, the organic metal catalyst is one or more of an organic zinc compound, an organic tin compound, and an organic bismuth compound, such as but not limited to one or more of bismuth isooctanoate, bismuth neodecanoate, bismuth cyclohexaneate, stannous octoate, and dibutyltin dilaurate.

[0040] In some embodiments, the cellulose modified polyurethane foam further comprises a film attached to the cellulose modified polyurethane foam. In some embodiments, the film is made of at least one of PET and release paper.

[0041] In some embodiments, the mixing step is as follows:

[0042] The non-fat-soluble cellulose or its derivative and deionized water are mixed and allowed to stand, and then isocyanate, an amine catalyst and a foam stabilizer are added and mixed to obtain a first mixed material;

[0043] The polyether polyol and the organic metal catalyst are mixed and then stirred with the first mixed material to obtain a second mixed material.

[0044] In the present application, non-fat-soluble cellulose or its derivatives are first mixed with deionized water, and then fully mixed and stirred with isocyanate, amine catalyst and foam stabilizer, so that the water-containing cellulose or its derivative particles are fully dispersed in the first mixed material. At the same time, the water molecules fully captured by the cellulose or its derivatives allow the first mixture system to start foaming reaction in advance in this environment. When the carbon dioxide gas generated by foaming is uniform and slightly dissipated, a mixed polyether polyol and an organic metal catalyst are added to perform a gel reaction. At this time, the cellulose or its derivatives also react with the isocyanate, so that the cross-linking degree of the foam is improved, and the viscosity around the cellulose or its derivatives increases rapidly, which plays a role in stabilizing the foam. After heating and curing, a cellulose-modified polyurethane foam with uniform and stable pores and high cohesion is obtained.

[0045] It is to be understood that the present application does not limit the above-mentioned mixing method, which may be but is not limited to stirring. In some embodiments, the above-mentioned mixing speed is 3000rpm~4000rpm, and the mixing time is 2min~5min. In practical applications, increasing or decreasing the speed and extending or shortening the mixing time according to the different adaptability of the mixing method are all within the protection scope of the present application.

[0046] In some embodiments, the standing time is 2 min to 3 min.

[0047] In some embodiments, the stirring and mixing speed is 8000 rpm to 10000 rpm, and the stirring and mixing time is 5s to 8s.

[0048] In some embodiments, the heating and curing steps are as follows:

[0049] The second mixed material is heated and solidified to obtain cellulose-modified polyurethane foam.

[0050] In a specific embodiment of the present application, the specific operation of the above-mentioned heating and curing is: applying the above-mentioned second mixed material to the surface of the substrate for heating and curing. It should be noted that the present application does not limit the above-mentioned "application" method, which can be but is not limited to calendar coating, brushing, dipping, spraying, roller coating, and scraper coating. In some embodiments, the above-mentioned second mixed material is applied to the surface of the substrate by coating. In some embodiments, the thickness of the above-mentioned coating is 0.2mm to 0.8mm.

[0051] In some embodiments, the substrate may be, but is not limited to, a PET film or a release paper. In practical applications, the polyurethane foam and the PET film may be peeled off before use, or the polyurethane foam and the PET film may not be peeled off.

[0052] In some embodiments, the temperature of the heating and curing is 80° C. to 110° C., and the time of the heating and curing is 15 min to 20 min.

[0053] The present application also provides the use of the cellulose modified polyurethane foam in electronic devices. It is understood that the electronic devices include but are not limited to portable electronic devices and precision electronic devices.

[0054] It should be understood that materials with the same or similar types, models, qualities, properties or functions as the reagents and instruments used in the following examples can be used to implement the present application. The experimental methods used in the following examples and comparative examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples and comparative examples can be obtained from commercial sources unless otherwise specified.

[0055] The following are examples and comparative examples:

[0056] Example 1

[0057] The components of the polyurethane foam provided in this embodiment are as follows:

[0058] 4.6g carboxymethyl cellulose (product model BH-1, the molar ratio of the hydroxyl group of carboxymethyl cellulose to the isocyanate group of isocyanate is 8:100), 0.3g deionized water, 8mg triethylene diamine, 4g double-terminal hydroxypropyl silicone oil (molecular weight of 1680, product model SH-2), 10g toluene diisocyanate (TDI), 10g liquefied diphenylmethane diisocyanate (MDI), 40g polyoxyethylene diol with 1,4-butanediol as initiator (molecular weight of 600, product model NBS-1012), 40g polyoxyethylene triol with propylene glycol as initiator (molecular weight of 1000, product model NBH-5022) and 4mg bismuth octanoate (product model SD-2). The viscosity of the polyether polyol mixture is 800mPa.s.

[0059] The preparation method of the above-mentioned polyurethane foam is as follows:

[0060] S1. Powdered carboxymethyl cellulose and deionized water were mixed, stirred at 4000 rpm for 2 min, and allowed to stand for 3 min to obtain a soil-like slightly viscous dispersion.

[0061] S2. Mix the above dispersion with TDI, MDI, triethylenediamine and double-terminated hydroxypropyl silicone oil, and stir at a rotation speed of 3000 rpm for 5 minutes to obtain a first mixed material.

[0062] S3, stirring the polyether polyol mixture and bismuth octanoate at a rotation speed of 3500 rpm for 4 min, and then stirring with the first mixed material at a rotation speed of 9000 rpm for 7 s to obtain a second mixed material.

[0063] S4. The second mixed material is coated on a PET film with a coating thickness of 0.5 mm, and then heated and cured at 90° C. for 17 min to obtain a cellulose-modified polyurethane foam with high cohesiveness.

[0064] Example 2

[0065] The components of the polyurethane foam provided in this embodiment are as follows:

[0066] 2.5g hydroxypropyl cellulose (product model BT-2, the molar ratio of the hydroxyl group of hydroxypropyl cellulose to the isocyanate group of isocyanate is 5:100), 0.3g deionized water, 6mg N,N-dimethylethanolamine, 5g foam stabilizer Y-10366, 15g toluene diisocyanate (TDI), 15g liquefied diphenylmethane diisocyanate (MDI), 35g polyoxyethylene-propylene copolymer glycol (molecular weight 800, product model ANS-1050) with ethylene glycol as initiator, 35g polyoxyethylene triol (same as Example 1) with glycerol as initiator and 4mg bismuth neodecanoate. The viscosity of the polyether polyol mixture is 800mPa.s.

[0067] The preparation method of the above-mentioned polyurethane foam is as follows:

[0068] S1. Powdered hydroxypropyl cellulose and deionized water were mixed, stirred at 3000 rpm for 3 minutes, and allowed to stand for 2 minutes to obtain a soil-like, slightly viscous cellulose solution.

[0069] S2. Mix the cellulose solution with TDI, MDI, triethylenediamine and bihydroxypropyl silicone oil, and stir at a speed of 4000 rpm for 3 minutes to obtain a first mixed material.

[0070] S3, mixing the polyether polyol mixture and bismuth octanoate, stirring at a rotation speed of 3000 rpm for 5 min, and then stirring with the first mixed material at a rotation speed of 10000 rpm for 5 s to obtain a second mixed material.

[0071] S4. The second mixed material is coated on a PET film with a coating thickness of 0.2 mm, and then heated and cured at 80° C. for 20 min to obtain a cellulose-modified polyurethane foam with high cohesiveness.

[0072] Example 3

[0073] The components of the polyurethane foam provided in this embodiment are as follows:

[0074] 5.2g cellulose (product model N-2, the molar ratio of hydroxyl group of cellulose to isocyanate group of isocyanate is 10:100), 0.3g deionized water, 8mg triethanolamine, 6g double-terminal hydroxypropyl silicone oil (same as Example 1), 13.5g liquefied diphenylmethane diisocyanate (MDI), 13.5g hexamethylene diisocyanate (HDI), 36.5g polyoxyethylene glycol with 1,4-butanediol as initiator (same as Example 1), 36.5g polyoxyethylene triol with glycerol as initiator (same as Example 1) and 4mg bismuth cyclohexane acid. The viscosity of the polyether polyol mixture is 1200mPa.s.

[0075] The preparation method of the above-mentioned polyurethane foam is as follows:

[0076] S1. Powdered cellulose and deionized water were mixed, stirred at 4000 rpm for 2 min, and allowed to stand for 3 min to obtain a soil-like, slightly viscous cellulose solution.

[0077] S2. Mix the cellulose solution, MDI, HDI, triethylenediamine and bihydroxypropyl silicone oil, and stir at a speed of 3500 rpm for 4 minutes to obtain a first mixed material.

[0078] S3, mixing the polyether polyol mixture and bismuth octanoate, stirring at a rotation speed of 3500 rpm for 4 min, and then stirring with the first mixed material at a rotation speed of 80000 rpm for 8 s to obtain a second mixed material.

[0079] S4. The second mixture is coated on a PET film with a coating thickness of 0.8 mm, and then heated and cured at 110° C. for 15 min to obtain a cellulose-modified polyurethane foam with high cohesive force.

[0080] Example 4

[0081] The components of the polyurethane foam provided in this embodiment are as follows:

[0082] 4.0g hydroxypropyl cellulose (product model BT-2, the molar ratio of the hydroxyl group of hydroxypropyl cellulose to the isocyanate group of isocyanate is 8:100), 0.3g deionized water, 6mg triethylenediamine, 4g double-terminal hydroxypropyl silicone oil (same as Example 1), 26.5g liquefied diphenylmethane diisocyanate (MDI), 73.5g polyethylene glycol with 1,4-butanediol as the initiator (same as Example 1) and 4mg dibutyltin dilaurate. The viscosity of the polyether polyol is 700mPa.s.

[0083] The preparation method of the above-mentioned polyurethane foam is as follows:

[0084] S1. Powdered hydroxypropyl cellulose and deionized water were mixed, stirred at 4000 rpm for 2 min, and allowed to stand for 3 min to obtain a soil-like, slightly viscous cellulose solution.

[0085] S2. Mix the above cellulose solution with MDI, triethylenediamine and bihydroxypropyl silicone oil, and stir at a rotation speed of 3000 rpm for 5 minutes to obtain a first mixed material.

[0086] S3. Mix the polyether polyol and dibutyltin dilaurate, stir at a rotation speed of 3500 rpm for 4 min, and then stir with the first mixed material at a rotation speed of 9000 rpm for 7 s to obtain a second mixed material.

[0087] S4. The second mixed material is coated on a PET film with a coating thickness of 0.5 mm, and then heated and cured at 90° C. for 17 min to obtain a cellulose-modified polyurethane foam with high cohesiveness.

[0088] Example 5

[0089] The components of the polyurethane foam provided in this embodiment are as follows:

[0090] 5.5g methylcellulose (product model H-2, the molar ratio of the hydroxyl group of methylcellulose to the isocyanate group of isocyanate is 8:100), 0.3g deionized water, 6mg triethylenediamine, 4g N,N-dimethylcyclohexylamine, 30g liquefied diphenylmethane diisocyanate (MDI), 70g polyoxyethylene triol (molecular weight 400, product model NBH-3022) with glycerol as initiator and 5mg stannous octoate. The viscosity of the polyether polyol is 300mPa.s.

[0091] The preparation method of the above-mentioned polyurethane foam is as follows:

[0092] S1. Mix powdered methyl cellulose and deionized water, stir at 3000 rpm for 3 minutes, and let stand for 2 minutes to obtain a soil-like, slightly viscous cellulose solution.

[0093] S2. Mix the cellulose solution, MDI, triethylenediamine and bihydroxypropyl silicone oil, and stir at a speed of 4000 rpm for 3 minutes to obtain a first mixed material.

[0094] S3, mixing the polyether polyol and stannous octoate, stirring at a rotation speed of 3000 rpm for 5 min, and then stirring with the first mixed material at a rotation speed of 10000 rpm for 5 s to obtain a second mixed material.

[0095] S4. The second mixed material is coated on a PET film with a coating thickness of 0.5 mm, and then heated and cured at 80° C. for 20 min to obtain a cellulose-modified polyurethane foam with high cohesiveness.

[0096] Example 6

[0097] The components of the polyurethane foam provided in this embodiment are as follows, and the preparation method is the same as that in Example 1:

[0098] 1.8g carboxymethyl cellulose (product model BH-2, the molar ratio of the hydroxyl group of carboxymethyl cellulose to the isocyanate group of isocyanate is 3:100), 0.2g deionized water, 6mg triethylene diamine, 6g double-terminal hydroxypropyl silicone oil (same as Example 1), 18g liquefied diphenylmethane diisocyanate (MDI), 18g hexamethylene diisocyanate (HDI), 32g polyoxyethylene diol with 1,4-butanediol as initiator (same as Example 1), 32g polyoxyethylene triol with glycerol as initiator (same as Example 1) and 4mg bismuth octanoate (same as Example 1). The viscosity of the polyether polyol mixture is 800mPa.s.

[0099] Example 7

[0100] The components of the polyurethane foam provided in this embodiment are as follows, and the preparation method is the same as that in Example 1:

[0101] 8.8g carboxymethyl cellulose (product model BH-2, the molar ratio of the hydroxyl group of carboxymethyl cellulose to the isocyanate group of isocyanate is 14:100), 0.4g deionized water, 6mg triethylene diamine, 6g double-terminal hydroxypropyl silicone oil (same as Example 1), 18g liquefied diphenylmethane diisocyanate (MDI), 18g hexamethylene diisocyanate (HDI), 32g polyoxyethylene glycol with 1,4-butanediol as initiator (same as Example 1), 32g polyoxypropylene triol with propylene glycol as initiator (molecular weight of 1000, product model NBH-7022) and 4mg bismuth octanoate (same as Example 1). The viscosity of the polyether polyol mixture is 800mPa.s.

[0102] Example 8

[0103] The components of the polyurethane foam provided in this embodiment are as follows, and the preparation method is the same as that in Example 1:

[0104] 4.3 g hydroxypropyl cellulose (the molar ratio of the hydroxyl group of the hydroxypropyl cellulose to the isocyanate group of the isocyanate is 7:100), 0.3 g deionized water, 8 mg triethylene diamine, 8 g double-terminal hydroxypropyl silicone oil (same as in Example 1), 20 g liquefied diphenylmethane diisocyanate (MDI), 80 g polyoxyethylene triol with glycerol as the initiator (same as in Example 5) and 5 mg dibutyltin dilaurate. The viscosity of the polyether polyol is 280 mPa.s.

[0105] Example 9

[0106] The components of the polyurethane foam provided in this embodiment are as follows, and the preparation method is the same as that in Example 1:

[0107] 5.2g cellulose (product model BT-2, the molar ratio of hydroxyl group of cellulose to isocyanate group of isocyanate is 8:100), 0.3g deionized water, 8mg triethylenediamine, 8g double-terminal hydroxypropyl silicone oil (same as Example 1), 15g liquefied diphenylmethane diisocyanate (MDI), 15g hexamethylene diisocyanate (HDI), 10g polyoxyethylene diol with 1,4-butanediol as initiator (same as Example 1), 60g polyoxyethylene triol with glycerol as initiator (same as Example 1) and 4mg bismuth octanoate (same as Example 1). The viscosity of the polyether polyol mixture is 1600mPa.s.

[0108] Example 10

[0109] The components of the polyurethane foam provided in this embodiment are the same as those in Example 1, and the preparation method is as follows:

[0110] S1. Powdered carboxymethyl cellulose and deionized water were mixed, and stirred at 4000 rpm for 2 min to obtain a soil-like slightly viscous cellulose solution, which was allowed to stand for 3 min.

[0111] S2. Stir the cellulose solution, the polyether polyol mixture and bismuth octanoate at a rotation speed of 3000 rpm for 5 minutes to obtain a first mixed material.

[0112] S3. Stir the first mixed material, TDI, MDI, triethylenediamine and bihydroxypropyl silicone oil at a rotation speed of 9000 rpm for 7 seconds to obtain a second mixed material.

[0113] S4. The second mixed material is coated on a PET film with a coating thickness of 0.5 mm, and then heated and cured at 90° C. for 17 min to obtain a cellulose-modified polyurethane foam.

[0114] Comparative Example 1

[0115] The components of the polyurethane foam provided in this comparative example are as follows:

[0116] 0.25g deionized water, 6mg triethylenediamine, 4g double-terminal hydroxypropyl silicone oil (same as in Example 1), 33g liquefied diphenylmethane diisocyanate (MDI), 12g polyoxyethylene glycol with 1,4-butanediol as initiator (same as in Example 1), 55g polyoxypropylene triol with glycerol as initiator (molecular weight of 1000, product model NBH-7022) and 5mg stannous octoate. The viscosity of the polyether polyol mixture is 1000mPa.s.

[0117] The preparation method of the above-mentioned polyurethane foam is as follows:

[0118] S1. Mix deionized water, MDI, triethylenediamine and double-terminated hydroxypropyl silicone oil, and stir at a rotation speed of 4000 rpm for 3 minutes to obtain a first mixed material.

[0119] S2. Mix the polyether polyol mixture and stannous octoate, stir at a rotation speed of 3000 rpm for 5 min, and then stir with the first mixed material at a rotation speed of 10000 rpm for 5 s to obtain a second mixed material.

[0120] S3. The second mixed material is coated on a PET film with a coating thickness of 0.5 mm, and then heated and cured at 80° C. for 20 min to obtain a polyurethane foam.

[0121] Comparative Example 2

[0122] The components of the polyurethane foam provided in this comparative example are as follows, and the preparation method is the same as that of Example 1:

[0123] 4.6g ethyl cellulose (product model E-2, the molar ratio of the hydroxyl group of ethyl cellulose to the isocyanate group of isocyanate is 7:100), 0.3g deionized water, 8mg triethylene diamine, 4g double-terminal hydroxypropyl silicone oil (same as Example 1), 10g toluene diisocyanate (TDI), 10g liquefied diphenylmethane diisocyanate (MDI), 40g polyoxyethylene diol with 1,4-butanediol as initiator (same as Example 1), 40g polyoxyethylene triol with glycerol as initiator (same as Example 1) and 4mg bismuth octanoate (same as Example 1). The viscosity of the polyether polyol mixture is 800mPa.s.

[0124] The properties of the foam prepared in the example were tested, and the testing method was as follows:

[0125] 1) Density measurement: overlap a 50 mm × 50 mm square mold, a polyurethane foam sample, and a pad, use a compression device to press a 50 mm × 50 mm fixed thickness sample, weigh it, and calculate the density by weight / (thickness × area).

[0126] 2) Compression strength measurement: refer to standard ASTM3574-2017 Test C, use a universal tensile testing machine, compression rate 5mm / min, and record the stress under 25% compression strain.

[0127] 3) Adhesive peeling test: Refer to the standard GB / T2792-2014, peel off the PET film on the surface of the protective film, and then stick it to the smooth surface of the foam sample. Use a 2Kg roller to roll back and forth three times at a uniform speed to prevent air residue from entering between the protective film and the foam. Keep the roller force consistent for each group of samples. Cut the sample with the protective film into 25mm wide strips, peel off part of the foam and protective film, clamp the protective film in a clamp of the tensile testing machine, and flip the foam 180° and clamp it with another clamp. Operate the tensile testing machine at a rate of 300mm / min to peel the protective film from the foam, obtain the test curve, and measure the peeling strength. The protective film is a PET release film with a gram weight of 5-8g / in, and the peeling force test value between the protective film and the standard steel plate is 5-8g.

[0128] 4) Cell diameter test: Cut the polyurethane foam into 50 mm × 50 mm pieces as the foam sample. Immerse the foam sample in liquid nitrogen for 1 min, and then cut it in the thickness direction of the sample using a razor blade. Take a magnified photo of the cross section using a digital microscope, and measure the cell diameters of all bubbles in the cross section with a length of 2 mm. Repeat the operation 5 times to obtain the maximum pore diameter AS. max , minimum aperture AS min , aperture difference = AS max -AS min .

[0129] The test results are shown in Table 1.

[0130] Table 1 Properties of polyurethane foam prepared in Examples 1 to 10 and Comparative Examples 1 to 2

[0131]

[0132]

[0133] The experimental results show that by adding non-fat-soluble cellulose or its derivatives, and controlling the hydroxyl value of non-fat-soluble cellulose or its derivatives and the molar ratio of the isocyanate group of isocyanate, the viscosity of polyether polyol, etc., the pores of the prepared cellulose-modified polyurethane foam are uniform, stable, and evenly dispersed. Multiple interconnected microscopic pores can disperse tensile stress and prevent temporary defects caused by stress concentration. At the same time, the molecular chain segments of the above-mentioned cellulose-modified polyurethane foam have sufficient toughness. When subjected to external tension or shear stress, the molecular structure can support macroscopic elastic deformation, and has high toughness and high cohesion, which is suitable for portable electronic devices and precision electronic devices.

[0134] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A cellulose-modified polyurethane foam with high cohesion, characterized in that: The cellulose modified polyurethane foam is obtained by mixing cellulose or its derivatives, isocyanate, amine catalyst, foam stabilizer, polyether polyol, organic metal catalyst and deionized water and then heating and curing. The cellulose or its derivative is non-fat-soluble cellulose or its derivative.

2. The cellulose-modified polyurethane foam according to claim 1, characterized in that: The molar ratio of the hydroxyl group of the non-fat-soluble cellulose or its derivative to the isocyanate group of the isocyanate is (5-10):

100.

3. The cellulose-modified polyurethane foam according to claim 1, characterized in that: The viscosity of the polyether polyol is 300mPa.s to 1200mPa.s.

4. The cellulose-modified polyurethane foam according to claim 3, characterized in that: The molar ratio of the hydroxyl value of the polyether polyol to the isocyanate group of the isocyanate is (90-95):100; The polyether polyol is selected from one or more of polyethylene oxide glycol with 1,4-butanediol as initiator, polyethylene oxide triol with glycerol as initiator, polypropylene oxide triol with glycerol as initiator and polyethylene oxide-propylene copolymer glycol with ethylene glycol as initiator.

5. The cellulose-modified polyurethane foam according to any one of claims 1 to 4, characterized in that: The isocyanate is one or more of toluene diisocyanate, liquefied diphenylmethane diisocyanate and hexamethylene diisocyanate.

6. The cellulose-modified polyurethane foam according to claim 1, characterized in that: The amine catalyst is one or more of triethylenediamine, N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl) ether, N,N,N',N'-tetramethylethylenediamine, triethylamine, N-ethylmorpholine, N-methylmorpholine, N,N-dimethylbenzylamine, N,N,N',N",N"-pentamethyldiethylenetriamine, N,N'-diethylpiperazine, N,N'-diethyl-2-methylpiperazine, N,N-dimethylethanolamine and triethanolamine; and / or, The organometallic catalyst is one or more of an organozinc compound, an organotin compound and an organobismuth compound; and / or, The foam stabilizer is one or more of bihydroxypropyl silicone oil, Y-10366 and gelatin.

7. The cellulose-modified polyurethane foam according to claim 1, characterized in that: The amount of deionized water added is 0.3wt% to 0.7wt% of the polyether polyol; and / or, The amount of the organic metal catalyst added is 0.005wt% to 0.007wt% of the polyether polyol; and / or, The amount of the amine catalyst added is 1.5wt% to 3wt% of the deionized water; and / or, The added amount of the foam stabilizer is 4wt% to 7wt% of the cellulose modified polyurethane foam.

8. The cellulose-modified polyurethane foam according to claim 1, characterized in that: The steps of mixing are as follows: The non-fat-soluble cellulose or its derivative and deionized water are mixed and allowed to stand, and then isocyanate, an amine catalyst and a foam stabilizer are added and mixed to obtain a first mixed material; The polyether polyol and the organic metal catalyst are mixed evenly and then stirred and mixed with the first mixed material to obtain a second mixed material.

9. The cellulose-modified polyurethane foam according to claim 8, characterized in that: The steps of heating and curing are as follows: The second mixed material is heated and cured to obtain cellulose-modified polyurethane foam; The temperature of the heating curing is 80° C. to 110° C., and the time of the heating curing is 15 min to 20 min.

10. Use of the cellulose modified polyurethane foam according to any one of claims 1 to 9 in electronic devices.

Citation Information

Cited By

  • Modified bio-based thin-layer soft polyurethane foam and preparation method thereof

    CN121045494A